MN PLAN - WILSON, PAT (Tufts Archival Research Center, 2007)
Confidential; Marginalia; Letter from Pat Wilson to Tina Walls regarding the Minnesota Labor Plan. Describes coalition efforts to combat a cigarette tax increase in Minnesota. Includes plans for a letter writing campaign, phone bank drive, media campaign, point-of-sale postcard campaign, and the development of CART- Citizens Against Regressive Taxation. Lists studies on the economic impact of cigarette and regressive taxes.